Advances in mechanical engineering : selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June, 2014 /: selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June, 2014. (2016) - Unknown
No abstract available